Use of power doppler for the assessment of vascularization in equine tendinitis treated with mesenchymal stem cells - Carvalho, Armando de Matos; Alvarez, Luiz E. C.; Oliveira, Patricia G. G.; Vendruscolo, Cynthia P.; Moroz, Andrei [UNESP]; Deffune, Elenice [UNESP]; Hussni, Carlos A.; Alves, Ana Liz Garcia (My University, 2014)
Tendinous lesions are very common in athlete horses. The process of tendon healing is slow and the quality of the new tissue is often inferior to the original, leading in many cases to recurrence of the lesion. One of the main reasons for the limited healing capacity of tendons is its poor vascularization. At present, cell therapy is used in equine practice for the treatment of several disorders including tendinitis, desmitis and joint disease. However, there is little information regarding the mechanisms of action of these cells during tissue repair. It is known that Mesenchymal Stem Cells (MSCs) release several growth factors at the site of implantation, some of which promote angiogenesis. Comparison of blood flow using power Doppler ultrasonography was performed after the induction superficial digital flexor tendon tendinitis and implantation of adipose tissue-derived MSCs in order to analyze the effect of cell therapy on tendon neovascularization. For quantification of blood vessel histopathological examinations were conducted. Increased blood flow and number of vessels was observed in treated tendons up to 30 days after cell implantation, suggesting promotion of angiogenesis by the cell therapy.